Using Hilbert Transform in Diagnostic of Composite Materials by Impedance Method - Eremenko, Volodymyr; Zaporozhets, Artur; Babak, Vitalii; Isaienko, Volodymyr; Babikova, Kateryna (Periodica polytechnica. Electrical engineering and computer science, 2020)
The article is devoted to the problem of the increasing of information quality for the impedance method of nondestructive testing. The purpose of this article is to get for the pulsed impedance method of nondestructive testing the additional informative parameters. Instantaneous values of the information signal's amplitude is a sensitive parameter to the effects of interference, in particular friction, which necessitates the use of additional informative features. It was experimentally measured signals from defective and defectless areas of the test pattern. Using of the Hilbert transform gave possibility to determine phase characteristics of these signals and realize demodulation to extract a low-frequency envelope for further analysis of its shape. It was received the informative features as a result of researches. Among them are instantaneous frequency of a signal, the integral of a phase characteristic on the selected interval and the integral of a difference signal phase characteristics. In order to compare quality of the defect detection using selected parameters it was carried out evaluation of the testing result reliability for a product fragment made of a composite material. Considering the influence of the change in the mechanical impedance of the researched area on the phase-frequency characteristics of the output signal of the converter, it is proposed to use as the diagnostic signs: the instantaneous frequency and the value of the phase characteristic of the current signal for certain points in time. The proposed informative features enable to increase general reliability of composite materials testing by the pulsed impedance method.